1999
DOI: 10.1080/089583799196754
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Inhalation Toxicology of Two Fiberglasses and Amosite Asbestos in the Syrian Golden Hamster. Part Ii. Results of Chronic Exposure

Abstract: Fiberglass (FG) is the largest category of man-made mineral fibers (MMVFs). Many types of FG are manufactured for specific uses building insulation, air handling, filtration, and sound absorption. In the United States, > 95% of FG produced is for building insulation. Several inhalation studies in rodents of FG building insulation have shown no indication of pulmonary fibrosis or carcinogenic activity. However, because of increasing use and potential for widespread human exposure, a chronic toxicity/carcinogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 57 publications
0
42
0
Order By: Relevance
“…Amosite used in this study was from the same batch as used in previous studies (Hesterberg et al, 1997, 1999a,b; McConnell et al, 1999; Rogers et al, 1999). …”
Section: Introductionmentioning
confidence: 99%
“…Amosite used in this study was from the same batch as used in previous studies (Hesterberg et al, 1997, 1999a,b; McConnell et al, 1999; Rogers et al, 1999). …”
Section: Introductionmentioning
confidence: 99%
“…The length distribution of the aerosol was consistent with that of the pre-Cyclotec processed chrysotile sample. Amosite used in this study was from the same batch as used in previous studies (Hesterberg et al, 1997(Hesterberg et al, , 1999aMcConnell et al, 1999;Rogers et al, 1999).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Similarly, it is worthy of note that in the rodent fiber inhalation bioassays conducted to date, pleural inflammatory and fibroproliferative lesions were accompanied by pulmonary parenchymal changes. Recently, there have been a number of chronic studies that suggested that the Syrian golden hamster may be particularly susceptible to the development of pleural mesothelioma as well as of pleural fibroproliferative changes following asbestos and synthetic vitreous fiber inhalation (Everitt et al, 1997;Gelzleichter et al, 1999;Mast et al, 1994;McConnell et al, 1999).…”
Section: Proposed Mechanisms For Asbestos-associated Non-neoplastic Pmentioning
confidence: 99%
“…Pleural fibrotic and inflammatory lesions develop in rodents in response to inhaled fibers, but these have not been categorized into separate lesion types as is the case in humans and often have not been described separately from pulmonary parenchymal fibrosis by toxicologic pathologists. It is noteworthy that significant pleural lesions similar to human pleural fibrotic lesions were found in chronic rodent inhalation bioassays with synthetic vitreous fibers as well as with asbestos fibers (McConnell et al, 1999).Mesothelial cells, resident and elicited inflammatory cells, and pleural fibroblasts are believed to be important effector cells in the pathogenesis of asbestos-induced nonneoplastic pleural diseases. Mesothelial progenitor cells may also participate in pleural repair and disease (Herrick & Mutsaers, 2004).…”
mentioning
confidence: 99%